Identifikasi dan Mitigasi Risiko Rantai Pasok Produk menggunakan Metode House of Risk (HOR) pada IKM Makanan - Nurwahidah, Andi; Nur, Alfian (Industrial Engineering Study Program, Pattimura University, 2025)
IKM S is one of the small and medium enterprises (SMEs) in the food sector, particularly focusing on the production of soy sauce, chili sauce, and vinegar. One of the challenges faced in its supply chain is the shortage of bottle raw materials from suppliers, resulting in reduced production and a high number of returned products due to expiration. This research aims to identify the risks in the supply chain and determine strategies to address these issues. The research methodology used is quantitative descriptive, employing the Supply Chain Operation Reference (SCOR) method to identify risk events and House Of Risk (HOR) for mitigation strategies. The study's findings indicate 21 risk events and 19 risk agents. In HOR 1, severity levels of risk events, occurrence frequencies of risk agents, and the relationship between risk events and agents were measured, resulting in an Aggregate Risk Potential value. Four risk agents causing issues in operational activities were identified. HOR 2 identified four preventive actions and prioritized mitigation based on the effectiveness versus implementation difficulty ratios of these actions for the company.